2001
DOI: 10.1086/318527
|View full text |Cite
|
Sign up to set email alerts
|

Twice‐Daily Triple Nucleoside Intensification Treatment with Lamivudine‐Zidovudine plus Abacavir Sustains Suppression of Human Immunodeficiency Virus Type 1: Results of the TARGET Study

Abstract: This open-label, multicenter, single-arm clinical trial assessed the 48-week efficacy of a twice-daily triple nucleoside reverse-transcriptase inhibitor regimen containing a lamivudine (150 mg)-zidovudine (300 mg) combination tablet (COM) and abacavir (ABC; 300 mg) in 87 antiretroviral therapy-experienced, protease inhibitor-naive patients infected with human immunodeficiency virus type 1 (HIV-1). At baseline, the median plasma HIV-1 RNA level was 3.10 log(10) copies/mL, and the median CD4 cell count was 506 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 14 publications
3
12
0
Order By: Relevance
“…Our study also showed that HIV-1 RNA undetectability was more likely to be achieved in antiretroviral-naive patients with baseline HIV-1 RNA levels of !100,000 copies/mL than it was in patients with baseline levels of у100,000 copies/mL (76% vs. 40% at week 24, determined by use of the 50-copy/mL assay); similar findings in association with COM-abacavir have been reported elsewhere [7]. These results may be because patients with lower pretreatment HIV-1 RNA levels potentially have better immunological function [11].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Our study also showed that HIV-1 RNA undetectability was more likely to be achieved in antiretroviral-naive patients with baseline HIV-1 RNA levels of !100,000 copies/mL than it was in patients with baseline levels of у100,000 copies/mL (76% vs. 40% at week 24, determined by use of the 50-copy/mL assay); similar findings in association with COM-abacavir have been reported elsewhere [7]. These results may be because patients with lower pretreatment HIV-1 RNA levels potentially have better immunological function [11].…”
Section: Discussionsupporting
confidence: 60%
“…In NZTA4006, Thompson et al [19] previously found that interruptions in abacavir dosing are not associated with an increased risk of hypersensitivity reaction. The apparent lack of clinically significant effects of COM-abacavir on serum levels of lipids and glucose seen in this study is noteworthy because it has likewise been observed in other clinical trials of this triple-nucleoside combination, which have had durations of up to 48 weeks [4,7]. Several teams of investigators have found that, when twicedaily doses of COM-abacavir are substituted for HAART regimens because patients have had hyperlipidemia and hyperglycemia, it can result in reversion of these abnormalities [20][21][22].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…ABC is phosphorylated by a novel enzymatic pathway (15) which might contribute to its activity in resting cells. In the initial clinical trials, ABC appeared more potent than other nucleoside analogs (33,40), and subsequent clinical experience corroborates the earlier data (22,25,28). Whether this in vivo activity is related to its activity in resting (or latently infected) cells is an intriguing possibility which will require additional studies.…”
Section: Discussionsupporting
confidence: 63%
“…Although the triple NRTI regimen was inferior to efavirenz-containing arms, it did suppress HIV-1 RNA to <50 copies/mL in 61% of patients at week 48. Similarly, TARGET [19], a single-arm trial of twice-daily 3TC/AZT/ABC, showed HIV-1 RNA suppression to <50 copies/mL in 56% of patients. Finally, NZTA4007 [20], a single-arm trial of 3TC/AZT/ABC, achieved HIV-1 RNA suppression to <50 copies/mL in 75% of patients at 24 weeks.…”
Section: Discussionmentioning
confidence: 99%